2013
DOI: 10.1002/ajh.23590
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid‐dependent procoagulant activity is highly expressed by circulating microparticles in patients with essential thrombocythemia

Abstract: This study evaluates the functional procoagulant features of plasma MP in order to explore the MP contribution to the hypercoagulable state of patients with Essential Thrombocythemia (ET). Platelet-free plasma samples were obtained from 73 ET patients (37 positive for the JAK2V617F mutation) and 72 control subjects. The calibrated automated thrombogram (CAT) was performed in plasma samples to determine thrombin generation of MP-associated tissue factor (TF) and procoagulant phospholipid (PPL) activity, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 25 publications
2
42
0
1
Order By: Relevance
“…Furthermore, we observed a tendency towards a higher PPL activity in the larger particles (Figure 4 (b)). The removal of 20K pellets and 100K pellets revealed a reduced activity of PPL in the subsequent supernatants (Figure 5), similar to findings by Marchetti et al [15]. Our findings indicated that EVs from healthy persons carry no or a very low amounts of TF, but contain some PPL which is also in agreement with the findings of others [28,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we observed a tendency towards a higher PPL activity in the larger particles (Figure 4 (b)). The removal of 20K pellets and 100K pellets revealed a reduced activity of PPL in the subsequent supernatants (Figure 5), similar to findings by Marchetti et al [15]. Our findings indicated that EVs from healthy persons carry no or a very low amounts of TF, but contain some PPL which is also in agreement with the findings of others [28,29].…”
Section: Discussionsupporting
confidence: 92%
“…This has been tested in patients with thrombosis or cancer [13,14]. Marchetti and co-workers [15] reported evidence of procoagulant phospholipid (PPL) activity in thrombocythemia patients using a combination of TGA and a PPL activity assay. However, the methods available to study the procoagulant effect of EVs retain certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the JAK2V617F mutation is associated with the increased occurrence of thrombosis in MPN patients (29)(30)(31). Marchetti et al (32) showed that ET patients with the JAK2V617F mutation were more procoagulant than patients without the mutation, and that JAK2V617F was the major determinant that contributes to increased thrombin generation. However, to the best of our knowledge, no previous study has addressed the association between the JAK2V617F mutation, MPs and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The V617F allele burden is known to be associated with acquired activated protein C resistance, low free PS and increased levels of soluble markers of endothelial and platelet activation including elevated tissue factor [5][6][7]. It also correlates with less conventional biomarkers of risk, including C-reactive protein, the inflammatory marker pentraxin-3 and circulating micro-particles and reticulated platelets [8][9][10]. Intriguingly, an inherited JAK2 46/1 haplotype may modulate thrombotic risk in some patients without the acquired mutation as well [11].…”
mentioning
confidence: 99%
“…Perturbations are known of several cellular elements (both quantitative and qualitative abnormalities of red and white cells, platelets and endothelial cells), subcellular humoral mediators (coagulation pathways and their inhibitors, intercellular adhesion molecules, secondary mediators, inflammatory cytokines and their metabolites) as well as rheological aspects including shear stress and hyperviscosity [2,[5][6][7][8]10]. The biological links between the genetic events and the ultimate macromolecular and cellular phenotypes is not always clear-cut but advances are underway.…”
mentioning
confidence: 99%